Governments' functions in the process of integrated consolidation and allocation of rural–urban construction land in China. (December 2015) - Tang, Ying; Mason, Robert J.; Wang, Yubo
Abstract: This paper explores key issues associated with integrated consolidation and allocation of rural–urban construction land (ICARUCL) in China. Based on a critical review of the literature and analysis of selected case studies, we identify barriers to effective ICARUCL implementation, which result principally from shortcomings in governance at the central and local levels. A framework for more effective governmental functions, aimed at addressing the challenges associated with the ICARUCL process, is then developed. We argue that better integration of government functions is required, in order to address such concerns as widely divergent socio-economic development levels within metropolitan regions and diverse desires and needs of relevant stakeholders. Key areas of concern regarding effectiveness of the ICARUCL implementation process are the external institutional environment, allocation of public goods among stakeholders, and overall organization and coordination.